Development of "Smart Literacy" Media Based on Tri-Nga Integrated Ethnomathematics in Elementary School Geometry Learning: Validity and Practicality Study - Khasanah, Siti Toifatun; Sukiyanto, Sukiyanto; Pardimin, Pardimin; Nisa, Ana Fitrotun; Al Masjid, Akbar (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
This study aims to develop Smart Literacy media based on Tri-Nga integrated ethnomathematics in elementary school geometry learning and to determine the level of validity and practicality of the developed media. This study uses a research and development (R&D) approach with the ADDIE model which limits it to four stages, namely analysis, design, development, and implementation. In the analysis stage, it is carried out through analysis of needs, student characteristics, curriculum, and local cultural potential. In the design and development stage, it has produced Smart Literacy media that integrates the ethnomathematics context and the Tri-Nga stages (ngerti-ngrasa-nglakoni). The validity of the media in this study was carried out by material experts, media experts, and language experts. The validation results show that the media obtained a percentage of 92.8% from material experts, 96.8% from media experts, and 91.6% from language experts, where all are in the very valid category. The implementation stage was carried out through a limited trial involving 3 teachers and 9 students to determine the level of practicality of the media. The results of a limited trial indicate that the Smart Literacy media is highly practical. This media is able to present geometry learning through the integration of local cultural contexts and comprehensive learning, encompassing cognitive, affective, and psychomotor aspects. Thus, the Smart Literacy media is declared valid and practical, and suitable for use as a geometry learning medium in elementary schools. This research is recommended for further testing the media's effectiveness on a broader scale and for developing similar media for other mathematics materials.